From snake pits to cash cows : politics and public institutions in New York - Castellani, Paul J., 1942- (Book collections on Project MUSE., 2005)
"Public institutions for people with developmental disabilities continue to operate within New York State, although their very existence has been condemned, and public policies directed their complete closure by the year 2000. From Snake Pits to Cash Cows investigates why these institutions persevere despite virtually universal predictions of their demise. Paul J. Castellani's provocative account spans the years 1935 to 2000, describing decades of conflict and confusion about the role of public institutions. This book demonstrates how and why a convergence of operational, fiscal, and political crises in the mid-1970s resulted in a series of agreements among adversaries that radically changed the political landscape, and reversed the plan to close all public institutions. He also shows why New York's experience has implications and lessons for the study of public policy in the area of developmental disabilities services and for understanding Medicaid policymaking, intergovernmental finance, and human services administration."--Jacket.